Does Depth Matter? Factors Affecting Choice of Vulvoplasty Over Vaginoplasty as Gender-Affirming Genital Surgery for Transgender Women. Issue 6 (26th April 2018) - Jiang, David; Witten, Jonathan; Berli, Jens; Dugi, Daniel
Abstract: Background: Gender-affirming vaginoplasty aims to create the external female genitalia (vulva) as well as the internal vaginal canal; however, not all patients desire nor can safely undergo vaginal canal creation. Aim: Our objective is to describe the factors influencing patient choice or surgeon recommendation of vulvoplasty and to assess the patient's satisfaction with this choice. Methods: Gender-affirming genital surgery consults were reviewed from March 2015 until December 2017, and patients scheduled for or who had completed vulvoplasty were interviewed by telephone. Outcomes: We report demographic data and the reasons for choosing vulvoplasty as gender-affirming surgery for patients who either completed or were scheduled for surgery, in addition to patient reports of satisfaction with choice of surgery, satisfaction with the surgery itself, and sexual activity after surgery. Results: In total, 486 patients were seen in consultation for trans-feminine gender-affirming genital surgery: 396 requested vaginoplasty and 39 patients requested vulvoplasty. 30 Patients either completed or are scheduled for vulvoplasty. Vulvoplasty patients were older and had higher body mass index than those seeking vaginoplasty. The majority (63%) of the patients seeking vulvoplasty chose this surgery despite no contra-indications to vaginoplasty. The remaining patients had risk factors leading the surgeon to recommend vulvoplasty. Of those who completed surgery, 93% were satisfied with the surgery and their decision for vulvoplasty. Clinical Translation: Vulvoplasty creates the external appearance of female genitalia without creation of a neovaginal canal; it is associated with high satisfaction and low decision regret. Conclusions: This is the first study of factors impacting a patient's choice of or a surgeon's recommendation for vulvoplasty over vaginoplasty as gender-affirming genital surgery; it also is the first reported series of patients undergoing vulvoplasty only. Limitations of this study include its retrospective nature, non-validated questions, short-term follow-up, and selection bias in how we offer vulvoplasty. Vulvoplasty is a form of gender-affirming feminizing surgery that does not involve creation of a neovagina, and it is associated with high satisfaction and low decision regret.